Detection of circulating tumor DNA by digital droplet PCR in resectable lung cancer as a predictive tool for recurrence. (January 2021) - Gassa, Asmae; Fassunke, Jana; Schueten, Sarah; Kuhlmann, Luca; Scherer, Marie; Qien, Jie; Zhao, Yue; Michel, Max; Loeser, Heike; Wolf, Juergen; Buettner, Reinhard; Doerr, Fabian; et al.
Highlights: ctDNA is detectable in early-stage lung cancer. Digital droplet PCR is feasible for detection of ctDNA in plasma. ctDNA may be used as predictable tool for post-surgical recurrence. Abstract: Lung cancer is the leading cause of cancer-related mortality worldwide due to difficulties in early detection and high postsurgical recurrence rate. Current European Guidelines recommend follow-up via computerized tomography (CT) scans on regular basis within the first 2 years after radical surgical resection. Despite these efforts, recurrence rates remain high with 30–70 %. Therefore, it is imperative to develop predictive markers for metastases and postsurgical recurrence using minimally invasive methods. This prospective study aims at defining the feasibility of detecting circulating tumor DNA (ctDNA) in presurgical plasma samples of patients with lung cancer by digital droplet PCR. Resected tumor tissue and simultaneous blood samples were collected from 24 patients with lung cancer in stage I-IIIA (12 stage I, 8 stage II, 4 stage III). Genomic DNA from the tumor tissue samples were analyzed for hotspot mutations using a 17 gene panel next-generation sequencing (NGS) assay. CtDNA from corresponding plasma samples were analyzed using digital droplet PCR (ddPCR). Additionally, DNA sequencing results were correlated with patients' outcome. At least one somatic mutation was detected by NGS (96 %) in 23 of the tested tissue samples. DdPCR detected mutations in circulating cell-free DNA (ccfDNA) of nine patients' samples (9/23, 39 %). Postsurgical outcome analysis was performed for those patients who had received complete tumor resection (n = 21). Four of them suffered from an early relapse within the first two years after surgery, including two with detectable somatic mutations in ccfDNA during primary staging. Taken together, we showed that the 17 gene panel assay revealed in 23 of 24 patients at least one somatic mutation in the primary tumor by NGS. Tumor-specific mutation was detectable in 39 % from the blood of early stage lung cancer patients by ddPCR.